1999
DOI: 10.1080/00218839.1999.11100999
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison of lipids in some pollens and their phagostimulatory effects in honey bees

Abstract: Lipid extraction in honey bee collected corbiculum pollen from seven plant host species showed distinct differences in amounts of lipid within preferred/non-preferred honey bee pollens. Mean amounts of lipid in highly preferred pollens such as Brassica campestris var. Toria, Cosmos bipinnatus and Raphanus sativum were 20.3%, 19.4% and 17.8%, respectively, and in least preferred pollens such as Helianthus annuus and Petunia hybrida were 11.9% and 11.6%, respectively. The cumulative flabellogustatory responses f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 17 publications
1
24
0
2
Order By: Relevance
“…The values of lipids in bee-pollen could be arranged in an ascending order: date palm < alfalfa < rape < sunflower < summer squash, with significant (p<0.01) differences among them. The high lipid levels in summer squash, and sunflower pollen were confirmed by Singh et al (1999) for rape and sunflower, and Nicolson and Human (2013) for sunflower. The content of lipids found in our studies ranged from 1.82 to 5.38% DM.…”
Section: Discussionmentioning
confidence: 84%
“…The values of lipids in bee-pollen could be arranged in an ascending order: date palm < alfalfa < rape < sunflower < summer squash, with significant (p<0.01) differences among them. The high lipid levels in summer squash, and sunflower pollen were confirmed by Singh et al (1999) for rape and sunflower, and Nicolson and Human (2013) for sunflower. The content of lipids found in our studies ranged from 1.82 to 5.38% DM.…”
Section: Discussionmentioning
confidence: 84%
“…Pure Helianthus fed to honeybees reduced adult longevity (Schmidt et al, 1995) and resulted in a low development of hypopharyngeal glands of new workers (Pernal and Currie, 2000). Moreover Singh et al (1999) found antifeedant compounds in Helianthus lipids.…”
Section: Pollens and Protein Contentsmentioning
confidence: 99%
“…toria, 19,4% para Cosmos bipinnatus, 17,8% para Raphanus sativum, 11,9% para Helianthus annuus e 11,6% para Petunia hybrida (SINGH et al,1999).…”
Section: Introductionunclassified